The Role of Perceived Value as a Mediating Variable in the Relationship Between Employee Competence, Responsiveness and Store Atmosphere on Customer Satisfaction - Heni Widyaningrum; Ali; Mohamad Rifqy Roosdhani (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2026)
Objective – This study aims to analyze the influence of employee competence, responsiveness, and store atmosphere on customer satisfaction, with perceived value as a mediating variable at Madrasah Aliyah Negeri 1 Jepara. Design/Methodology/Approach – A quantitative approach with explanatory research design was employed. Data were collected through closed-ended questionnaires using a ten-point Likert scale distributed to 304 students who had received madrasah services within the last six months. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. Findings – The results indicate that responsiveness and store atmosphere positively and significantly affect perceived value and customer satisfaction, while employee competence has no significant direct effect. Perceived value significantly influences customer satisfaction and mediates the relationships between the independent variables and satisfaction. Implications – These findings suggest that customer satisfaction in educational services is strongly shaped by perceived value, highlighting the importance of enhancing service responsiveness and environmental factors to improve student satisfaction both theoretically and practically.